Pengaruh Harga, Biaya Promosi dan Biaya Personal Selling Terhadap Volume Penjualan Hino Dump Truck pada PT Gita Riau Makmur Pekanbaru - Satria, Gema; Sulistyowati, Lilis; ', Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in PT. Gita Riau Makmur Pekanbaru located on Jl. KH Nasution km. 12 Pekanbaru, using secondary data to collect data in the form of documentation, records and other data that supports research related to data rates, promotional costs, the cost of personal selling, and sales volume. The purpose of this study was to determine how the effect of simultaneous partial and variable prices, the cost of promotion, personal selling expenses to sales volume PT. Gita Riau Makmur Pekanbaru. Based on the results of the study indicate that either simultaneously or in partial price as (X1), the variable cost of promotion as (X2) and the cost of personal selling as (X3) significantly affect the sales volume variable (Y) products Hino Dump Truck in PT. Gita Riau Makmur Pekanbaru. The biggest price increases occurred in 2008 with a percentage of 48.81%. Although the percentage increase in the price of this aspect fluctuated. However, the increase in price in accordance with the features, reliability and excellence Hino Dump Truck products are furtherenhanced by the new technology brings different from other brand variants Promotional costs were highest in 2010 with a percentage of 44.96%. This is done to create attraction in terms of price, because in 2010 the company faced competitive pressures with the company. Personalselling costs were highest in 2007 which reached 62.90% this is because in 2007 there are some new products are launched, thus making the company more promotion costs and spend more to market the new product through personal selling efforts for more effective and capable inincreasing the sales of new products such as dealing directly with consumers. Advice can be given to the management is to maintain and increase the cost of the ad is scalable to be able to increase sales of the company, considering this variable is significant and positive effect on sales, prioritize budget on sales promotion activities, partially considering a more significant impact on sales compared with other variables.Keywords : Price, Promotion Cost, Personal Selling Costs and Sales Volume.